ANALYSIS OF G-MEAD HUMAN SELF DEVELOPMENT STAGE ON THE APPLICATION OF ONLINE LEARNING IN SMAS NUSANTARA BUNGAH: Analisis Tahap Pengembangan Diri (Self) Manusia G-Mead pada Penerapan Pembelajaran Online di Sekolah SMAS Nusantara Bungah - Isnaini Falihah Afriliyah Ali Hasby (SOSIOEDUKASI, 2020)
This policy means that all activities must change their orientation, that is, they may not go through face-to-face, including teaching and learning activities at various levels of education, both formal and informal. Teaching and learning activities continue, but must take advantage of-based media online or whatever form it takes as long as it is not face-to-face with the intention of avoiding the transmission of Covid-19 in Indonesia. This research is a type of qualitative research. The data analysis technique used in this study is a qualitative descriptive technique with critical theory studies supported by the stages of child development in the rationalization of technology as a scalpel. This research was conducted at SMAS Nusantara Bungah, which has implemented-based learning methods online during the pandemic. Therefore, macro and micro solutions are absolutely necessary to avoid the possibility of something worse happening. At the macro level, the government must immediately issue a new policy regarding a more humane learning model by providing supporting facilities and infrastructure. Then at the micro level, an intense dialogical relationship is needed to make the best use of technology between teacher-parents and teacher-students to solve grassroots problems.